Effects of Occupational Noise Exposure on Hearing Status, Blood Lipid and Hypertension Levels in Workers of a Fireclay Mine - Masoud Neghab; Hamid Karimi; Sayed Hamidreza Tabatabaee; Esmaeel Soleimani; Abas Ali Kasaeinasab (Shiraz University of Medical Sciences, 2014)
Background: Noise is one of the most pervasive hazards in industrial settings. This retrospective study was carried out to assess the effects of noise exposure on hearing status, blood lipids and blood pressure of employees of a local fireclay mine.Methods: Two hundred and forty male workers were studied. Data on audiometric measurements, blood lipids and blood pressure were derived from the workers' medical records and analyzed. Furthermore, area noise measurements were performed. Data were analyzed using SPSS version 16.0.Results: Workers were exposed to a mean noise level of 91±15 dB. The means of triglyceride (TG), total cholesterol (TC), systolic and diastolic blood pressure (SBP and DBP) were within the normal range for the first three years of the study. However, a slight, non-significant increase in TG level was noted in 2010. Most of the participants (63.6%) suffered from moderate hearing loss (HL). About 23.6% and 12.7% of the employees  had developed severe and mild HL, respectively. A statistically significant difference was noted in the number of workers with high-frequency noise-induced HL. Furthermore, a statistically significant association was found between the mean of high frequency HL and log-transformed TG values in 2009 and 2010.Conclusions: High frequency HL could be used as a biomarker for identifying workers exposed to excessive noise levels. High frequency HL developed over a 4-year exposure to noise was associated with hyper triglyceridemia. Implementing a hearing conservation program seems to be mandatory to prevent further increases in the number of workers who are already in the severe HL group.